A double sideband combined tracking method for Galileo E5 AltBOC signals - Tongwen Fan; Tisheng Zhang; Hongping Zhang; Jun Mo; Xiaoji Niu (Satellite Navigation, 2023)
Abstract The Galileo navigation satellite system (Galileo) E5 Alternative Binary Offset Carrier (AltBOC) signal brings various challenges due to its complex modulation, wide bandwidth, and multi-peaked auto-correlation function. While wideband tracking needs to solve the ambiguity problem and design dedicated baseband channels, the single-sideband cannot have the outstanding performance of the AltBOC signal. We propose a new tracking method called “Double Sideband Combined Tracking” (DSCT), which can fully exploit the AltBOC signal’s code tracking accuracy without ambiguity and ensure compatibility with Binary Phase Shift Keying (BPSK) processing channels, easily implemented in hardware. The DSCT employs one phase locked loop and one delay locked loop to track the carrier and code, respectively. The double-sideband correlation results used by the two loops are recovered by coherently combining the single-sideband correlation results of the two BPSK channels. Meanwhile, the combined model, the loop discriminator, and the ambiguity detection of the DSCT are discussed. Furthermore, the code tracking error caused by thermal noise is modeled and analyzed. The test results based on real Galileo E5 signals show that the DSCT exhibits better or comparable code tracking accuracy to the AltBOC wideband tracking method. When the loop falsely locks onto a side-peak, the DSCT can quickly detect and re-lock on the main peak.